SUMBER-SUMBER ILMU PENGETAHUAN DALAM MANAJEMEN PENDIDIKAN ISLAM - Erwin Indrioko (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Success in education when graduating superior and competent human resources in various fields. However, to achieve success in education must struggle in the science of management education. Islamic education management science is knowledge about governance of Islamic educational institutions that are obtained through scientific processes and arranged systematically as a truth that is recognized by many people. As subjects in the practice of Islamic education management, each individual must understand the sources of his knowledge. In the level of management of Islamic education there are various sources to gain knowledge, namely empiricism, rationalism, intuition, revelation. According to the empiricism, humans gain knowledge through their life experiences. Medium rationalism is a flow that considers that reason is the most important medium for gaining knowledge. Intuition is a flow that considers the ability to understand the science of management education without going through rational reasoning but through whispers of hearts and gestures. Revelation is called the pure source of all knowledge that comes from God, revelation contributes to the building of knowledge that is not affordable by rational and empirical forces. The scientific method is a procedure in gaining knowledge. Broadly speaking the steps of the scientific method are the formulation of the problem, the preparation of the framework of thinking in the submission of hypotheses, the formulation of hypotheses, testing hypotheses, and drawing conclusions.